2015
DOI: 10.1242/dev.121962
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid hormone nuclear receptor TRα1 controls the Notch signaling pathway and cell fate in murine intestine

Abstract: Thyroid hormones control various aspects of gut development and homeostasis. The best-known example is in gastrointestinal tract remodeling during amphibian metamorphosis. It is well documented that these hormones act via the TR nuclear receptors, which are hormone-modulated transcription factors. Several studies have shown that thyroid hormones regulate the expression of several genes in the Notch signaling pathway, indicating a possible means by which they participate in the control of gut physiology. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…In particular, Hairy1, but not the other genes analyzed, was significantly up‐regulated even after 1 day of T3 treatment. However, Hairy1 may still be indirectly regulated by T3 as reported in the mouse intestine , because its up‐regulation by T3 was impaired by Notch inhibition. Hairy2b is also considered to be a TH‐indirect response gene, since its expression was not up‐regulated until 4 days after T3 treatment.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, Hairy1, but not the other genes analyzed, was significantly up‐regulated even after 1 day of T3 treatment. However, Hairy1 may still be indirectly regulated by T3 as reported in the mouse intestine , because its up‐regulation by T3 was impaired by Notch inhibition. Hairy2b is also considered to be a TH‐indirect response gene, since its expression was not up‐regulated until 4 days after T3 treatment.…”
Section: Discussionmentioning
confidence: 91%
“…As mentioned above, the Notch pathway maintains the NSC pool in the adult SVZ and is also required for OPC generation in the embryo . Moreover, Notch signalling responds to THs . Thus, in the adult, Notch‐induced inhibition of fission might be involved in the reduced activation of DRP1 in SVZ‐OPCs .…”
Section: Implications Of Cell Metabolism On Neurogenesis and Th‐inducmentioning
confidence: 92%
“…It is worth to underline that complex cross-regulations between T 3 /TRα and key signalling pathways including Wnt, Notch and BMP have been largely described in the intestinal epithelium, where T 3 /TRα controls the balance between cell proliferation and cell differentiation of the crypt precursor cells (Plateroti et al 2006, Sirakov et al 2015. Interestingly, studies in human HCC showed that KLF9 expression is downregulated compared with the normal liver counterpart, and that exogenous KLF9 expression inhibits proliferation of HCC cell lines and their tumourigenic capacity when xenografted in immunodepressed mice (Sun et al 2014).…”
Section: T 3 /Trs Axis and Cell Differentiationmentioning
confidence: 99%